Impacts of Decentralization on Environmental Management in Thailand - JARUSOMBAT, SOPARATANA (Universitas Muhammadiyah Yogyakarta, 2010)
This paper describes the process, institutional and legal framework within which the environmentalmanagement operates in Thailand. It specifically focuses on the decentralization within central andlocal government’s role in environmental management. The methods of this research use literaturereview. The aim of the paper is to examine how interface between the central and local loci of powerhave affected pieces of legislation relating to management of the environment by central and localgovernment in Thailand.